Odpowiedzi

2009-11-14T14:06:43+01:00
A) 2¼ : 1½ + ⅙= 9/4 : 3/2 + 1/6 =
9/4 * 2/3 + 1/6 = 3/2 + 1/6 = 9/6 + 1/6 = 10/6 = 1 4/6 = 1 2/3

Odp: 1 ⅔

b) ⅗ + ⅖ : 0,3 = 5/5 : 3/10 = 1 * 10/3 = 10/3 = 3 1/3

Odp: 3 ⅓
Najlepsza Odpowiedź!
2009-11-14T14:14:59+01:00
A) 2¼ : 1½ + ⅙= 9/4 : 3/2 + 1/6 = 9/4 : 9/6 + 1/6= 9/4 :10/6= 9/4 razy 6/10=27/20= 2 i 7/20
b)⅗ + ⅖ : 0,3 =5/5 razy 10/3 = 10/3 = 3 i 1/3
c) (6 ⅖ - 5 ⁷/₁₀) * (8⅓ - 1⅘)= (32/5 - 57/10) razy(25/3 - 9/5)=
(64/10 - 57/10) razy (125/15 - 27/5)=7/10 razy 98/15= 343/75=
4i 43/74